Des bidonvilles aux sites de relogement à Témara : la quête d’une identité urbaine légitime - Aziz Benkorti (L’Année du Maghreb)
The devaluing image associated with slums leads to a feeling of stigmatisation among their inhabitants. For some slum dwellers, rehousing is imagined as a new start, an opportunity to take on an urban identity that is legitimate in their eyes, by accessing legal and decent housing. This intended identity is constructed in interaction with the authorities and non-residents of the slums, and is associated with a legitimate urban status. Through a qualitative sociological survey, this article studies how the quest for a new urban identity in the Nasr neighbourhood, a collective housing project designed to rehouse former residents of Témara, has created logics of exclusion and social hierarchisation. It analyses the effects of place, the logics of exclusion and the techniques mobilised by stigmas in order to understand neighbourhood relations and the relations maintained by the ex-bidonvillois with the rest of the city. The aim is to find out whether the rehousing of former slum dwellers has enabled them to overcome the feeling of stigmatisation felt in the slums. The article is structured in three parts. The first part provides a description of the neighbourhood studied and the conditions of settlement. Built within the framework of the national ‘Cities without Slums’ (CSB) programme, the Nasr neighbourhood reflects the neoliberal urban governmentality promoted by the World Bank for Development. A policy contributing to the fabrication of the indebted poor. For some ex-slum dwellers, rehousing is experienced as a form of ruralization, as it is located far from the city centre and its amenities, which were accessible in the slum context. The deterioration of the social conditions of this population fuels a certain hostility and discontent towards the authorities. The second part of the article highlights the precarious living conditions for a large proportion of ex-bidonvillians. Indeed, the flats were a disillusionment for some ex-bidonvillians in relation to their expectations. This is largely linked to the authorities’ objective of deconstructing habitats considered to be both a spatial and social evil without putting in place a more adequate social support strategy that meets the expectations of the population. The feeling of abandonment due to the lack of social support has given rise to subaltern means of resistance such as associative work, individual and collective mobilisation, indignation towards the public authorities, and the construction of an informal market to respond to their needs. The precarious transition from the slums to the resettlement area has worsened the economic and social situation of some inhabitants. At the economic level, many families, particularly the most disadvantaged (women heads of household and some ex-slum dwellers working in day jobs), have difficulty in covering new expenses, such as bank bills, water and electricity costs. Finally, the third part analyses the social relations within the neighbourhood. Flats were allocated arbitrarily, which led to a breakdown in the existing social ties between the slum dwellers. Moreover, the departure of some ex-slum dwellers and the arrival of other social categories created a social hierarchy based on the amount of economic capital owned and the attempts to adapt to the new life. This has led to a kind of mistrust and social withdrawal. Although this social hierarchy is invisible to the outside world, the inhabitants of the neighbourhood are seen as homogeneous and judged according to the image that others have of their neighbourhood. This leads the inhabitants to want to flee the neighbourhood in order to distinguish themselves and to appropriate a new urban identity.